The Effect of Addition of Triclosan Antibacterial Agent on The Setting Time of Glass Ionomer Cement - Egi Utia Asih; Martha Mozartha; Billy Sujatmiko (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Glass ionomer cement (GIC), restorative material in dentistry, are composed of glass powders and polyacrylic acid. GIC can release fluoride that acts as an antibacterial. Various study had been conducted to improve that antibacterial properties, but it can affect the physical and mechanical properties of GIC. The purpose of this study was to determine the effect of addition of triclosan antibacterial agent on the setting time of GIC. To obtain 2.5 % triclosan, 0,25 gram of triclosan powder was mixed into 9,75 gram of GIC powder. The sample was divided into 2 groups: control group (n=16) and treatment group (n=16). The setting time was measured using gilmore needle, by penetrating a needle to the surface of specimens with an interval of 10 seconds until the needle left no traces on the surface of specimens. Statistical analysis was done byT-test. The result showed that p value > 0,05. The conclusion is the addition of triclosan antibacterial agent do not affect the setting time of GIC